Front Cover: Controlling the Emergence and Shift Direction of Mechanochromic Luminescence Color of a Pyridine‐Terminated Compound (Chem. Asian J. 3/2019). Issue 3 (16th January 2019) - Kondo, Mizuho; Yamoto, Taku; Miura, Seiya; Hashimoto, Mayuko; Kitamura, Chitoshi; Kawatsuki, Nobuhiro
Abstract : A pyridine‐terminated fluorescent luminophore has been synthesized that exhibited mechanochromic luminescence (MCL) when combined with an acid. Although the luminophore showed both blue and red shifts in the photoluminescence spectra upon mechanical grinding with different acid species, it exhibited little mechanoresponsiveness itself. Furthermore, compounds with similar molecular backbones to the dye/acid complex were synthesized to clarify the color‐change mechanism. The compounds showed both blue and red shifts in the photoluminescence spectra and diffuse reflectance spectra upon grinding, indicating that the aggregation structure plays an important role in the mechanoresponsive behavior rather than the π‐conjugated structure. More information can be found in the Full Paper by Mizuho Kondo, Nobuhiro Kawatsuki et al. onpage 471 in Issue 3, 2019 (DOI:10.1002/asia.201801647 ).